Adjustment Problems of Working and Nonworking Women in Contrast of Their Husband: A Comparative Study of Marital Adjustment Issues among Working and Nonworking Women in Jaipur (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In truth, marriage is a lifestyle. This is not always rosy nonetheless, its success is contingenton both parties' capacity to modify. Adjustment and marital relationships are important issues in mostfamilies as the percentage of dual-career families grows. The focus of this research was to discover themarital adjustment issues that non-working women and working women teachers in Jaipur encounter. Atotal of 80 women are chosen at random (40 non-working women and their husbands, and 40 workingwomen instructors and their spouses). Data was collected using the Marital Adjustment Jnventorycreated by Dr. Harmohan Singh, Department of Psychology, R. B. S. College, Agra (1987). In compared totheir partners, non-working wives have higher marital adjustment issues, according to the findings.Second, working women instructors are more likely than non-working women to have marital adjustmentissues. Working women, we might argue, may suffer from the more severe reasons for maladjustment atwork or at home due to extra duties of their jobs.